(3aJM GdYRjR TQM GdhLjRs - (3YHO GdcQje Hf eMeO Hf YHO GdcQje, CHh GdbGSe GdQGaYj GdbRhjfj,J (B623 (3g` s; (3GdZRGdj , MLI GdESdGe CHh MGeO eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3cJGH GdQgf s
(3BNQgG (B:s
(3BNQ cJGH GdaQGFV s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B312 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2002s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs